2018
DOI: 10.1021/acs.cgd.7b01661
|View full text |Cite
|
Sign up to set email alerts
|

Accessing Phase-Pure and Stable Acetaminophen Polymorphs by Thermal Gradient Crystallization

Abstract: We employ a simple and reproducible methodology based on thermal gradient crystallization to access forms I and II of acetaminophen. This methodology provides insight into the role of heat flux in the control over polymorphism and phase transitions. We report the crystallization of different polymorphs of acetaminophen as a function of the thermal gradient parameters (magnitude of the gradient, sample velocity) in a thin film geometry. The thin-film samples were displaced at well-defined velocities (1 ≤ v ≤ 75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Previous work has shown that the effective magnitude of the temperature gradient (G exp ) that forms between the hot and cold zones is less than the magnitude simply calculated by the equation G = (T h À T c )/x, where x = 2.0 mm is the gap between the hot and cold stages. [27][28][29][30] The calibration of the DT setup has been carried out as previously reported 30 and is detailed in the ESI, † (Table S1 and Fig. S1).…”
Section: Crystal Growth Morphology Calculationmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work has shown that the effective magnitude of the temperature gradient (G exp ) that forms between the hot and cold zones is less than the magnitude simply calculated by the equation G = (T h À T c )/x, where x = 2.0 mm is the gap between the hot and cold stages. [27][28][29][30] The calibration of the DT setup has been carried out as previously reported 30 and is detailed in the ESI, † (Table S1 and Fig. S1).…”
Section: Crystal Growth Morphology Calculationmentioning
confidence: 99%
“…1). [27][28][29][30] This technique, also known as directional crystallization or solidification, is essentially an adaptation of the method of Percy Bridgman to thin films of molecular compounds using the set-up invented by Kenneth Jackson. 31 Although this technique has commonly been used for the study of organic compounds such as n-alkanes and m-nitroaniline, [32][33][34][35][36] it has not widely been applied to control the crystalline morphology of OSC thin films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, thermal analysis requires less amount of the sample 2-4 mg with longer detection time 20-30 minutes or more depend on the targeted process with easier detection of the polymorphic mixture [22]. Other characterization methods are: Raman spectroscopy [36] , polarized light microscopy [37] , FTIR [38] and many others.…”
Section: Characterization Of Phase Transformationmentioning
confidence: 99%
“…It is well-known that the pharmacokinetic properties of drugs are very closely related to the crystal form. Recently, extensive studies have been conducted to improve relevant properties of active pharmaceutical ingredients (APIs) via crystal engineering including polymorphism and crystal morphology control 1,2 and cocrystallization. 3−6 Cocrystals deserve particular attention, due to the wide range of potential coformers, which can be utilized for tuning the physicochemical properties of APIs.…”
Section: ■ Introductionmentioning
confidence: 99%